Online Dating: Market or Bazaar? The Marriage Partner Search Process on an Orthodox Dating Site - Kristina Galitsina; Polina Kalinovskaya; Olga Khvorostianova (Journal of Economic Sociology, 2022)
According to a number of researchers, in view of the marketization of culture, the processes of searching for and choosing a romantic partner have taken on the characteristics of a market which becomes especially apparent in case of online dating platforms [Heino Ellison, Gibbs 2010; Schmitz 2017]. The logic of religious dating platforms, where the proclaimed goal is to find a spouse once and for good, may conflict with the market integration logic of a platform itself. In this study, based on the in-depth semi-structured interviews with 18-35-year-old Orthodox online dating platform users from Moscow and the Moscow region, the objective is to identify the form of integration that is suitable for describing the search for a couple on this site. Firstly, the search for a partner is studied through G. Akerlof's perspective as search on the market so that the website’s questionnaire and photos are treated as institutional mechanisms used to tackle the problem of imperfect information and the quality uncertainty. Secondly, the search process in hand is considered as a bazaar in line with C. Geertz’s argument where messaging is bargaining, and users, motivated by the desire to find a soulmate, aim at clientelization. Finally, the authors infer that the bazaar perspective is more relevant for describing the search process in the considered case. In conclusion, the market angle itself is problematized, and attention is also paid to the functioning of the platforms in general.